The Effect of Geochemical Elements on Resistivity Values in Nickel Laterite Profiles (Case Study: Area "YL", Pomalaa District, Kolakaa Regency, Southeast Sulawesi - Baiq Yola Wahyu Febryanty; Y Yatini; Muhammad Arief Wicaksono (Journal of Geology Sriwijaya, 2023)
Indonesia is located in the meeting zone of the world's three major plates, causing Indonesia to be an area with high tectonic activity. One of the products of this activity is the large number of economic mineral resources in several regions in Indonesia, one of which is nickel. Indonesia is one of the highest nickel producers in the world, with production reaching 11,887 tons of ore resources. The level of demand for nickel has increased quite rapidly in recent years, thus encouraging exploration activities to continue. The nickel laterite zone produces several deposits, such as top soil, limonite, saprolite, and bedrock. In exploration activities, the saprolite zone is the main target due to its high nickel content. The exploration stage was carried out by applying one of the geophysical methods, namely the Electrical Resistivity Tomography (ERT) method. This research uses 4 (four) 300 meter ERT lines and Wenner configuration, as well as drill and geochemical data to assist in the analysis process. The aim of this research is to determine the characteristics of each zone of nickel laterite deposits which are controlled by the levels of elements or compounds they contain. Based on the research results, the range of resistivity values obtained is quite low, namely low (< 35 Ωm) is the saprolite zone, medium (35 – 65) Ωm is the saprock zone which contains boulders in it, and high (> 65 Ωm) is the bedrock zone in the form of Peridotite rocks, most of which have undergone quite intensive serpentinization and weathering processes and are influenced by tectonic activity in the form of faults. Resistivity values are largely influenced by the levels of metal elements and water (H2O), especially in the saprolite and saprock zones. This is controlled by the morphology and movement of water below the surface, thus influencing the weathering process that occurs, causing unevenness in the thickness and distribution of elements and compounds in each zone in the research area.